Formasio Liturgi demi Implementasi Pembaharuan Liturgi Konsili Vatikan II: Sebuah Studi Dokumen Gereja Desiderio Desideravi - Stenly Vianny Pondaag; Antonius Tukiran (Media: Jurnal Filsafat dan Teologi, 2023)
This paper aims to explain the role of liturgical formation in the context of implementing the liturgical renewal of the Second Vatican Council. The author wants to analyze the latest document of Pope Francis, Desiderio Desideravi, which speaks about the liturgical formation of the faithful. This paper is designed as a document analysis. developing their liturgical competence, namely the ability to understand and experience the deep meaning of liturgical simbols. This document also presents Pope Francis' efforts to support the spirit of liturgical renewal of the Second Vatican Council. Discussions about the liturgy cannot be separated from the understanding of the Church (ecclesiology). This document states that the spirit of liturgical renewal is inseparable from the understanding of the Church as the People of God.